Citizenship in Asian history. Issue 3 (3rd April 2019) - Bijl, Paul; van Klinken, Gerry
ABSTRACT: This article introduces a special issue of Citizenship Studies in which historians of East, South and Southeast Asia continue the project of globalizing citizenship by analyzing practices and conceptions of citizenship in pre-colonial China, India and Indonesia. Building on the recent global turn in citizenship studies as well as historicizing this turn, we shift the conceptual focus from formal membership and contracts to practices and acts of citizenship. Against citizenship essentialism, conceptual room is created for different ways in which people across Asia have participated in ruling and being ruled, employing different vocabularies, institutions and practices that showed they had agency in the polities they lived in. The main conclusion is that forms of citizenship participation can be found everywhere in Asian history, and were often anchored in practices which were both structural and effective.